Effect of nutrition education received by teachers on primary school students' nutrition knowledge - Elmas, Cemre; Arslan, Perihan (Korean Nutrition Soc, 2020)
BACKGROUND/OBJECTIVES: The aim of this study was to assess the effect of nutrition education received by fourth- and fifth-grade teachers in state schools in Famagusta, Northern Cyprus, on their students. SUBJECTS/METHODS: The aim of this study is to assess the effect of nutrition education received by fourth- and fifth-grade teachers (n = 27) in state schools in Famagusta on their students. Participants (n = 718) were selected through a regional pilot scheme. The teachers were instructed on nutrition by the researcher and provided with a researcher-prepared nutrition education book I Am Learning about Healthy Nutrition. Before receiving their nutrition education, the teachers were pretested to assess their baseline nutrition knowledge. Following receipt of their nutrition education, a posttest, which included the same questions as those in the pretest, was administered to the teachers to assess the effectiveness of the training session. Similarly, students were asked pretest researcher-prepared questions to evaluate their baseline nutrition knowledge level. The teachers were then given a period of three to four weeks to instruct the students in nutrition education. Following this instructional period, a posttest that included the same questions as those in the pretest was administered to the students. RESULTS: The results showed that there were significant differences between the pre- and posttest scores of both teachers and students; in both groups, the nutrition knowledge level increased (P < 0.05). CONCLUSIONS: These results show that the provision of nutrition education training to teachers positively affected the nutrition knowledge level of both teachers and students.
Keywords: Education; training programs; healthy nutrition; primary school; children